Plausible structure of the iron-molybdenum cofactor of nitrogenase. - Madden, M S (1992)
A plausible structure of the iron-molybdenum cofactor of nitrogenase [reduced ferredoxin:dinitrogen oxidoreductase (ATP-hydrolyzing), EC 1.18.6.1] is presented based on altered substrate reduction properties of dinitrogenase containing homocitrate analogs within the cofactor. Alterations on each carbon of the four-carbon homocitrate backbone were correlated with altered substrate reduction properties of dinitrogenase containing these analogs. Altered substrate reduction properties are the basis for a model in which homocitrate is oriented about two cubane metal clusters.